2004
DOI: 10.1093/rheumatology/keh087
|View full text |Cite
|
Sign up to set email alerts
|

Blunted coronary flow reserve in systemic sclerosis

Abstract: CFR is often reduced in SSc patients. CFR was lower in patients with dSSc than in those affected by lSSc. A reduced CFR value should be considered an indirect sign of heart involvement in scleroderma, but its clinical and prognostic implications need to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
21
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 24 publications
4
21
0
3
Order By: Relevance
“…As for regional systolic function, in our SSc population, despite normal LV ejection fraction and DMI systolic peak velocities, a significant reduction of Strain and SR indexes at the level of both IVS and LV lateral free wall was detected, pointing out an early direct involvement of LV ventricular walls by the myopathic process, at a time when other global and regional systolic parameters remain normal. As for coronary and peripheral vascular function in SSc, the CFR impairment in our patients is likely to detect an anatomical and/or functional impairment in coronary microvasculature, because the presence of an involvement of small coronary arteries has been showed by others even in absence of abnormalities of epicardial coronary arteries [5,6]. However, further evidence is provided by our data that endothelial dysfunction in SSc patients is not confined to the coronary microcirculation, but also extends to large peripheral conduit arteries.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…As for regional systolic function, in our SSc population, despite normal LV ejection fraction and DMI systolic peak velocities, a significant reduction of Strain and SR indexes at the level of both IVS and LV lateral free wall was detected, pointing out an early direct involvement of LV ventricular walls by the myopathic process, at a time when other global and regional systolic parameters remain normal. As for coronary and peripheral vascular function in SSc, the CFR impairment in our patients is likely to detect an anatomical and/or functional impairment in coronary microvasculature, because the presence of an involvement of small coronary arteries has been showed by others even in absence of abnormalities of epicardial coronary arteries [5,6]. However, further evidence is provided by our data that endothelial dysfunction in SSc patients is not confined to the coronary microcirculation, but also extends to large peripheral conduit arteries.…”
supporting
confidence: 61%
“…Such involvement is historically classified into primary and secondary. Primary heart disease depends on the involvement of myocardium and microvascolature by SSc disease itself, with impairment of global diastolic function and reduction of coronary flow reserve, even in asymptomatic patients without abnormalities of epicardial coronary arteries [4][5][6]. Secondary form of cardiac disease develops in SSc patients with vascular and/or interstitial lung disease, in which the fibrotic process leads to major reduction in the cross-sectional area of pulmonary vascular bed due to obliteration of alveolar capillaries and/or narrowing of many small arteries [7,8].…”
mentioning
confidence: 99%
“…Noninvasive methods were used to asses subclinical atherosclerosis in SSc, including IMT and IBPI, with contradicting results [65,66]. Studying other variables such as traditional risk factors, disease duration, patients' age, the presence of anticentromer or antitopoisomerase antibodies, ANA, and the type of SSc (limited and diffuse and abnormalities in lung function tests), shows that only patients' age is associated to increase risk of atherosclerosis, an association opposed by some studies [67,68].…”
Section: Accelerated Atherosclerosis In Sscmentioning
confidence: 99%
“…Unlike microvascular disease, this has not been studied extensively. Impaired coronary artery reserve has previously been demonstrated in SSc patients by noninvasive imaging techniques (5)(6)(7). Studies published a few decades ago suggested an underlying microvascular disease of the myocardium, based on normal findings on coronary angiogram (8) and the absence of coronary atherosclerosis upon histologic examination at autopsy (9)(10)(11)(12).…”
mentioning
confidence: 99%